Nordic consensus document on Evolut FX+ transcatheter aortic valve implantation: optimizing index implantation and longer-term outcomes - Khokhar, Arif A.; Savontaus, Mikko; Al-Ani, Ahmed; Terkselsen, Christian Juhl; Bieliauskas, Gintautas; van der Heijden, Annemieke; Amin, Azad Alhasan Alhaj; James, Stefan; Russell, Kristoffer; De Backer, Ole (Frontiers in Cardiovascular Medicine, 2025)
Transcatheter aortic valve replacement (TAVI) is an established treatment strategy for patients with severe symptomatic aortic stenosis (AS). Multiple landmark randomized controlled trials have consistently demonstrated the safety, efficacy, and longer-term durability of the CoreValve/Evolut (Medtronic, MN, USA) transcatheter aortic valve (TAV) platform in treating severe AS. These findings have supported the expansion of TAVI to younger patients with longer life expectancy, in whom an optimized index valve implantation can significantly impact both acute procedural results and longer-term outcomes. In this technical narrative, we aim to describe how iterative changes in the latest-generation Evolut FX(+) TAV can be utilized to achieve an optimized index valve implantation.